PRODUCTION, PURIFICATION AND INHIBITION OF ALGINATE LY-ASE FROM LOCAL ISOLATE OF PSEUDOMONAS AERUGINOSA NA11 - Younis, R. W. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
The point of this study was for determine of the optimum conditions and purification of alginate lyase from local isolate of Pseudomonas aeruginosa NA11, and inhibition of enzyme by various plant extracts. Forty local  isolate s of pathogenic Pseudomonas aeruginosa were screened for their ability to produce alginate lyase. Local isolate of P.aeruginosa NA11 showed the maximum efficiency for produce of alginate lyase with high specific activity (14.4 U/mg). Several factors that influence on alginate lyase production from local isolate of P.aeruginosa NA11 were studied, these factors included the type of media, carbon source, nitrogen source, the incubation temperature, pH, and the incubation period. The highest yield of alginate lyase was obtained with the A medium supplemented with 0.5 % of glucose and sodium nitrate at pH 7.5 after 24 hr. incubation at 37 °C. Two chromatographic techniques were used for purification of alginate lyase after precipitation by ammonium sulphate with saturated ratio (0-70 %),  including, ion exchange chromatography by DEAE-cellulose and gel filtration by Sephadex G-100. The two steps gave the specific activity of 155.8 U/mg protein, the purification fold was 4.15 and enzymatic yield was 64 %. The molecular weight of partial purified alginate lyase was 57 KDa. The results of antioxidant activity tests for different plants extracts utilizing DPPH radical scavenging activity were showed that the saad extract has high antioxidant activity (71 %) more than other plants extracts. While the results for inhibition experiment of alginate lyase were demonstrated that saad extract was the best inhibitor with inhibition ratio of 86 %.